2014
DOI: 10.1007/s10120-014-0374-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-term quality of life after laparoscopic distal gastrectomy for early gastric cancer: results of a prospective multi-institutional comparative trial

Abstract: Background The aim of this study was to compare the postoperative health-related quality of life (HRQOL) between open and laparoscopic distal gastrectomy. Methods A multi-institutional nonrandomized study was conducted. Patients with clinical T1 gastric cancer were prospectively enrolled and underwent distal gastrectomy by either the open or laparoscopic approach. HRQOL was measured using the European Organization for Research and Treatment of Cancer, Quality of Life QuestionnaireCore 30 and the site-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 26 publications
1
35
1
2
Order By: Relevance
“…Postoperative QoL in patients receiving gastrectomy is dependent on the extent of the gastric resection, the reconstruction type, and the abdominal approach method [1213141516]. Because QoL is one of the overall flow indicators for managing patients following gastrectomy, it is important to understand long-term chronological QoL changes, in general, after gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative QoL in patients receiving gastrectomy is dependent on the extent of the gastric resection, the reconstruction type, and the abdominal approach method [1213141516]. Because QoL is one of the overall flow indicators for managing patients following gastrectomy, it is important to understand long-term chronological QoL changes, in general, after gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Although surgery is the standard curative treatment, it is among those that most affect quality of life and lead to distress . Surgery tends to cause a major deterioration in patients' health‐related quality of life (HRQoL) with a slow and long recovery . Between the presurgery and postsurgery stages, although patients report a stabilization of their anxiety level, they generally experience an increase in their depression symptoms .…”
Section: Introductionmentioning
confidence: 99%
“…The authors previously conducted a multi-institutional nonrandomized trial to compare the postoperative health-related QOL between open and laparoscopic distal gastrectomy using the European Organization for Research and Treatment of Cancer, Quality of Life Questionnaire-Core 30 [15]. We found that the postoperative 18 appetite loss reached the lowest value on POM 1 and gradually recovered thereafter.…”
Section: Discussionmentioning
confidence: 99%